Effect of organic additives on the mitigation of volatility of 1-nitro-3,3 `-dinitroazetidine (TNAZ): next generation powerful melt cast able high energy material - Talawar, M. B.; Singh, Alok; Naik, N. H.; Polke, B. G.; Gore, G. M.; Asthana, S. N.; Gandhe, B. R. (Journal of Hazardous Materials, 2006)
1-Nitro-3,3'-dinitroazetidine(TNAZ) was synthesized based on the lines of reported method. Thermolysis studies on synthesized and characterized TNAZ using differential scanning calorimetry (DSC) and hyphenated TG-FT-IR techniques were undertaken to generate data on decomposition pattern. FF-IR of decomposition products of TNAZ revealed the evolution of oxides of nitrogen and HCN containing species suggesting the cleavage of C/N-NO(2) bond accompanied with the collapse of ring structure. The effect of incorporation of 15% additives namely, 3-amino-1,2,4-triazole(AT), 3,5-diamino-1,2,4-triazole (DAT), carbohydrazide (CHZ), 5,7-dinitrobenzofuroxan (DNBF), bis (2,2-dinitropropyl) succinate (BNPS), triaminoguanidinium nitrate (TAGN), 2,4,6-trinitrobenzoic acid (TNBA) and nitroguanidine (NQ) on the volatility of TNAZ was investigated by undertaking thermogravimetric analysis. The TG pattern brings out the potential of BNPS and TAGN as additives to mitigate the volatility of TNAZ. The influence of additives on thermal decomposition of pattern of TNAZ was also investigated by DSC. The DSC results indicated that the additives did not have appreciable effect on the melting point of TNAZ. Scanning electron microscopic (SEM) studies were carried out to investigate the effect of additives on morphology of TNAZ. This paper also discusses the possible mechanism involved in between the TNAZ and TAGN and BNPS. It appears that the formation of charge transfer complex formation between the TNAZ and TAGN/BNPS. The effect of addition of high explosives such as CL-20, HMX and RDX on thermo-physical characteristics of TNAZ is also reported in this paper. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: melt castable explosive; morphological structure; synthesis; Thermolysis; trinitroazetidine (TNAZ); volatility behavior